ANALISIS KADAR MERKURI (Hg) DALAM URIN PENAMBANG EMAS TRADISIONAL (Studi Kasus di Desa Panton Luas Kecamatan Sawang Tapak Tuan, Aceh) - Harianto Bangun; Gusbakti Rusip; Zul Alfian (Pascasarjana Universitas Negeri Medan, 2015)
Abstract Mercury (Hg) can be exposed to the traditional gold miners during the screening process and annealed. In the filtering process of mercury (Hg) into the body through the skin. And in the process of annealed mercury (Hg) is heated at very high temperatures so that the mercury (Hg) will evaporate and enter the body through inhalation miners. This study aims to determine the amount of mercury (Hg) in the urine of traditional gold miners in the village of Panton Luas subdistrict sawwang southern Aceh district. This study was an observational study with a descriptive design. Sample of 30 people. Collecting data through laboratory tests and questionnaires and analyzed descriptively and analysis uniariat. The results showed that the levels of mercury (Hg) in the urine of gold miners still in the normal range is 4μg / l, an average of 2.82 (SD ± 0.57). Although still within normal limits need to do further research with a more representative sample so that the results will be more accurate. Kata kunci : Kadar Merkuri (Hg), Urin, Penambang Emas Tradisional